FORENSIC PSYCHIATRY PERSPECTIVE ON FIT-TO-WORK EXAMINATION PROCEDURE: A SYSTEMATIC REVIEW - Lestari, Ni Kadek Duti Ardi Suarjani Putri; Raharjanti, Natalia Widiasih; Riana, Henny (Journal of Psychiatry Psychology and Behavioral Research, 2025)
Introduction: Currently, there is a trend of increasing requests for fit-to-work examinations from several institutions regarding their mental health of employees, which are expected to provide some input for actions or decisions, such as termination due to their mental disorder, temporary permit leave, or other forms of assistance. This phenomenon was observed at Professor Dr. Soerojo Mental Health Hospital, Magelang, and Dr. Cipto Mangunkusumo General Hospital, Jakarta, as two hospitals that represent the work situations of the authors. This study aimed to search for a standardized FFD evaluation to release an accurate and objective forensic psychiatry report and minimize the risk of legal conflict and dispute. Methods: This qualitative systematic review used the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) method. The clinical question was formulated with the PICO model, which focuses on the fit-to-work examination procedure from a forensic psychiatry perspective. The search was conducted in PubMed, Scopus, ProQuest, PsycInfo, and Cochrane databases. Results: The search yielded 5 matched articles, which were then analyzed and compared to each other afterwards. The analysis included the steps of the fitness for duty examination procedure and the formulation of opinions based on the examination. Discuss: The stages involved in a psychiatrist's assessment of fitness for work include the examination stage and the formulation of examination results to form an opinion regarding fitness for work to produce an objective forensic psychiatric report. Conclusion: Clinician or forensic psychiatry team must take note of clear and concise examination in forensic psychiatry and give specific recommendations and advice to the referrer if therapy is required, including an explanation of the type and frequency of therapy needed and how recovery will occur. This will help the referrer understand exactly how an individual who is currently unfit for work can become fit for work in the future, as well as explain how symptoms of mental disorders can arise in the work environment and describe the early signs of recurrence.